Restating a research definition in conformance to soft systems semantics - Silva, J. (Implementation ? realizing operations management knowledge, XVI international annual conference of the EurOMA, 2009)
This study concerned the choice of SSM, shaped by both theory and other research findings. A conceptual model to position the assessment of Production Control Systems was introduced, considering criticism to used research methods. Then, an attempt to match SSM with the previously typified problem situation was done. Outcomes concern relevant modifications to the research purpose, coming from both the new semantics and innovative mindset. As a result of this challenge, clear changes to the writing style arose from different SSM meanings, despite no ‘optimal solutions’ were found.